Veterinarians' perspectives of pain, treatment, and diagnostics for bovine respiratory disease in preweaned dairy calves - Mijares, S.; Edwards-Callaway, L.; Roman-Muniz, I. N.; Coetzee, J. F.; Applegate, T. J.; Cramer, M. C. (Frontiers in Pain Research, 2023)
Bovine Respiratory Disease (BRD) is a leading cause of morbidity and mortality in preweaned dairy calves. Early detection and treatment are essential to minimize animal welfare concerns, particularly given that recent research also demonstrates that BRD is painful. Veterinarians are essential to ensuring calves with BRD receive appropriate treatment, but little to no research exists regarding veterinarians’ perspectives about BRD detection and treatment in dairy calves. This is a critical step to determine education and outreach needs that can target BRD treatment to improve calf welfare. Thus, the objectives of the current study were to describe US veterinarians’ current detection methods and treatment practices for BRD in preweaned dairy calves, understand veterinarians’ rationale for treatment decisions, and identify gaps in knowledge regarding treatment and management of calf BRD. An online survey was sent to two veterinarian-focused list-serves and newsletter. Final responses (n=47) were analyzed using qualitative and quantitative analyses. On-farm necropsy was the diagnostic tool most considered “extremely important” (26, 55.3%). All veterinarians indicated that BRD was at least mildly painful. However, only 53% of veterinarians (n=25) assess pain in preweaned calves with BRD in order to make treatment decisions. Furthermore, of the veterinarians that assessed pain, 40% (n=10) reported that their knowledge of pain assessment and treatment was adequate, but most (n=24) considered a calf’s pain-level at least “moderately important” to make BRD treatment decisions. The most important ancillary therapy for antimicrobials were NSAIDs (21, 44.7%). The ancillary therapy most often considered “extremely important” for treating BRD was NSAIDs. Qualitative analysis identified the following as factors that influenced veterinarians’ willingness to provide analgesia: the farm’s willingness to administer drugs, clinical signs, perceived severity of pain, the need for anti-inflammatories, and the presence of fever and comorbidities. This study included a small sample size and an extremely low response rate; results should therefore be interpreted with caution. Despite this limitation, important gaps in knowledge were identified, including pain assessment and consideration when making treatment decisions, and diagnostic tools. Addressing these needs in future research and outreach efforts could help ensure appropriate and timely treatment of calf BRD, including pain mitigation.